HUBUNGAN ANTARA DURASI PENYAKIT, FREKUENSI HOSPITALISASI DAN TINGKAT KEPARAHAN GEJALA DENGAN KEJADIAN PUTUS OBAT PADA PASIEN DENGAN GANGGUAN JIWA - Dian Fitria; Dhea Natashia; Tri Setyaningsih; Veronica Yeni (Husada Mahakam, 2023)
Psychological disorders are one of the chronic diseases that decrease patients' productivity and require long-term care and treatment. During the treatment process, patients often experience relapses due to the length of the treatment. One of the factors that can trigger relapse is medication discontinuation. Therefore, through this study, the researcher aims to obtain an overview of patients with mental disorders and relapse occurrences, as well as to determine the impact of medication discontinuation on the duration of mental illness, frequency of hospitalization, and severity of symptoms during relapse. This study is cross-sectional study involving 108 respondents. The analysis in this study utilized descriptive analysis and bivariate analysis using independent t-test. The results of this study indicate that one of the reasons family members bring patients to the hospital is the emergence of anger symptoms (26.1%), with medication discontinuation due to lack of patient medication adherence support being another common reason (23.5%). The research also shows a correlation between the duration of mental illness, frequency of hospitalization, severity of symptoms, and medication discontinuation in patients with mental disorders. Based on these findings, the involvement of family and effective discharge planning is crucial in reducing relapse rates and promoting rehabilitation towards independent and productive patient outcomes.